Nutrition transition and the risk of over-nutrition among female adolescents in Indonesia: analysis of Indonesian family life survey data 2007 and 2014 - Mulyaningsih, Tri; Shabrina, Amalina; Purwaningsih, Yunastiti; Sasanti, Ika Alicia (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Global changes and urbanisation cause nutrition transition which holds a crucial factor to nutritional status. Nutrition transition manifests in increased access to unhealthy and highly processed food, as well as reduced physical activity that may lead to over-nutrition.Objectives: This study aimed to measure the proportions of food consumption expenditure by food groups, identify nutrition transition by comparing the proportions of food expenditure namely modern, traditional, plant-based, meat-based, ready to eat and processed foods, and investigate association between nutrition transition and nutritional status of female adolescents in Indonesia.Materials and Methods: This study used secondary data from the Indonesian Family Life Survey 4 (2007) and 5 (2014) that collected data on individual food consumption in the past week. Nutrition transition was measured by comparing proportions of food expenditure to estimate consumption. Height, weight, and age were calculated into Body Mass Index-for-age (BMI-for-age) to identify nutritional status. Data from 5,203 female adolescents aged 12-18 years were used. Multiple Logistic regression was performed to estimate the Odds Ratio (OR).Results: Compared to 2007, there was an increase in the proportion of food expenditure for modern food and ready-to-eat food in households. On the other hand, the proportion of traditional food, plant-based food, and processed food consumption decreased in 2014 compared to 2007. Plant-based is a protective factor for over-nutrition (OR = 0.54; 95% CI: 0.31-0.95). Meanwhile, ready to eat food was a risk factor for over-nutrition (OR = 1.56; 95% CI: 0.95-2.57).Conclusion: Plant-based is a protective factor; while ready-to-eat is a risk factor for over-nutrition among female adolescents.Keywords : Female adolescents;nutrition transition; over-nutrition; plant-based; ready to eat meal